Research on the construction risk control technology of shield tunnel underneath an operational railway in sand pebble formation: a case study. Issue 10 (23rd August 2020) - Lei, Mingfeng; Lin, Dayong; Huang, Qiyou; Shi, Chenghua; Huang, Linchong
Abstract: It's inevitable that, various types of construction works emerge within proximity during the large-scale construction of urban rail transit, thus posing huge challenges for the actual construction. In this paper, a minute study on the construction risk control of shield tunneling beneath the existing railroads relying on a practical engineering is conducted, thereby developing a set of feasible risk-handling ideas, mainly including: (1) based on the detailed investigation and analysis of the engineering background and construction environment, to find out the key control indicators; (2) to carry out the risk assessment, and to identify the key factors influencing the engineering safety and environmental safety; (3) in view of the key risk factors, to propose purposeful measures for risk control; (4) to establish a numerical model to analyse the feasibility of risk control measures; and, (5) to establish a rigorous construction monitoring system for dynamically adjusting the construction parameters at real time and evaluating the engineering safety. So far as the practical engineering in this paper, the key risk sources are sand pebble stratum, delayed grouting and earth pressure in the chamber set incorrectly, and without proper control, these three factors may lead to large-area settlement and deformation during the construction. For this reason, targeted risk control program, covering rotary churning pile reinforcement, overhead line reinforcement (reinforcement by longitudinally lifting the existing railroad using cantilevers of I-beams) and shield driving parameter control, etc., are further proposed, and numerically simulated, with the construction monitoring and tracking results indicating that, under the protection of the above risk control measures, the settlements of roadbed and rail of existing railroads are less than 2 mm, which can meet the requirements in the railway operation safety. Finally, combining the actual construction situation, the empirical values of the optimised driving parameters for the shield going beneath the existing railroads in the water-rich sand pebble stratum are given, such as: driving speed is within range of 55 60 mm/min, earth pressure in the chamber is 0.13 MPa, the pressure for synchronous grouting is about 2.4 bars, which can be available reference for similar projects.